2009
DOI: 10.1007/s11284-009-0632-3
|View full text |Cite
|
Sign up to set email alerts
|

UV plumage color is an honest signal of quality in male budgerigars

Abstract: Elaborate and colorful feathers are important traits in female mate choice in birds. Plumage coloration can result from pigments deposited in feathers such as carotenoids and melanins, or can be caused by nanoscale reflective tissues (structurally based coloration), usually producing ultraviolet (UV) coloration. Structural colorations remain the least studied of the three most important feather colorations. Previous studies have found a female preference for UV color in the budgerigar, Melopsittacus undulatus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 56 publications
(61 reference statements)
4
33
0
Order By: Relevance
“…Birds relieved of parasites should have a less stimulated immune system, and may therefore invest more into beak coloration. Accordingly, several studies in birds have highlighted strong links between UV ornamentation and parasite load (Hõrak et al 2001;Mougeot et al 2005) or in a broader context immuno-competence (Griggio et al 2010). Here again, the independent changes we observe in UV or YO coloration support previous findings that in king penguins, UV and YO colors of the beak are produced by distinctly different mechanisms (Dresp and Langley 2006), and appear to change over the course of the breeding season.…”
Section: Beak Spot Coloration and Parasitessupporting
confidence: 89%
“…Birds relieved of parasites should have a less stimulated immune system, and may therefore invest more into beak coloration. Accordingly, several studies in birds have highlighted strong links between UV ornamentation and parasite load (Hõrak et al 2001;Mougeot et al 2005) or in a broader context immuno-competence (Griggio et al 2010). Here again, the independent changes we observe in UV or YO coloration support previous findings that in king penguins, UV and YO colors of the beak are produced by distinctly different mechanisms (Dresp and Langley 2006), and appear to change over the course of the breeding season.…”
Section: Beak Spot Coloration and Parasitessupporting
confidence: 89%
“…UV colouration can be indicative of phenotypic quality (Keyser and Hill 1999;Sheldon et al 1999;Doucet et al 2005;Griggio et al 2010b), supporting other evidence that UV may be a target of sexual selection. Mate choice relative to UV reflectance in pigmented-based colouration has received much less attention than structural plumage colouration.…”
Section: Influence Of Uv Reflectance In Mate Choicesupporting
confidence: 70%
“…Also, the interest in UV vision increased considerably due to its role in sexual signalling (Cuthill et al 2000a;Johnsen et al 1998;Sirkiä and Laaksonen 2009;Griggio et al 2010a), with two hypotheses being raised considering UV (1) as a special communication channel (Hausmann et al 2003) or (2) as just part of the overall colouration without a specific signalling role Stevens and Cuthill 2007). Several studies demonstrated a condition dependence in UV colouration (in blue grosbeaks, Guiraca caerulea, Keyser and Hill 1999; blue tits, Cyanistes caeruleus, Sheldon et al 1999; pied flycatchers, Ficedula hypoleuca, Siitari and Huhta 2002; black-capped chickadees, Poecile atricapillus, Doucet et al 2005; and in budgerigars, Melopsittacus undulatus , Griggio et al 2010b), suggesting that an individual variation in UV may be used in sexual signalling.…”
Section: Introductionmentioning
confidence: 99%
“…One aspect of individual quality that plumage coloration is frequently linked to is the ability to resist parasite infection or mount an immune response (Dunn et al, 2010;Kelly et al, 2012). While previous work focused largely on pigment-based, particularly carotenoid, coloration, recent work has shown that structural coloration may also be related to immunity or levels of parasitism (Doucet and Montgomerie, 2003;Bonato et al, 2009;Griggio et al, 2010). For example, in male satin bowerbirds (Ptilonorhynchus violaceus), brighter blue or greater UV chroma is associated with lower parasite loads (Doucet and Montgomerie, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Male ostriches (Struthio camelus) and south polar skuas (Catharacta maccormicki) with larger or more colorful white plumage patches mount a stronger humoral immune response (Bonato et al, 2009;Hanssen et al, 2009). Finally, stronger cutaneous immune responses [response to phytohemagglutinin (PHA) injection] have been associated with greater UV reflectance of green plumage in budgerigars (Melopsittacus undulates) (Griggio et al, 2010). Only recently have studies examined the relationship between female coloration and immunity and have primarily focused on white plumage patches.…”
Section: Introductionmentioning
confidence: 99%